2013
DOI: 10.1016/j.pneurobio.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Brain development in rodents and humans: Identifying benchmarks of maturation and vulnerability to injury across species

Abstract: Hypoxic-ischemic and traumatic brain injuries are leading causes of long-term mortality and disability in infants and children. Although several preclinical models using rodents of different ages have been developed, species differences in the timing of key brain maturation events can render comparisons of vulnerability and regenerative capacities difficult to interpret. Traditional models of developmental brain injury have utilized rodents at postnatal day 7–10 as being roughly equivalent to a term human infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

41
1,372
2
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,683 publications
(1,488 citation statements)
references
References 239 publications
41
1,372
2
11
Order By: Relevance
“…However, current approaches to model ZIKV infection in rodents results in lethality during pregnancy, although human babies survive and display microcephaly. In addition, a newly born mouse brain is relatively immature, akin to the developmental stage of the human brain at midgestation (Semple et al, 2013), and mouse brain development includes a major postnatal component. Thus, it has been suggested that examination of neurodevelopmental defects of ZIKV in mice requires postnatal analysis (Miner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, current approaches to model ZIKV infection in rodents results in lethality during pregnancy, although human babies survive and display microcephaly. In addition, a newly born mouse brain is relatively immature, akin to the developmental stage of the human brain at midgestation (Semple et al, 2013), and mouse brain development includes a major postnatal component. Thus, it has been suggested that examination of neurodevelopmental defects of ZIKV in mice requires postnatal analysis (Miner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The human gestational period is 280 days; rat gestation is 21 days (11). At birth, the human brain roughly corresponds to a postnatal day 7 rat brain based on body/brain weight ratios, and a 2-to 3-year-old human brain corresponds to a post natal day-20 rat brain (11).…”
Section: Introductionmentioning
confidence: 99%
“…At birth, the human brain roughly corresponds to a postnatal day 7 rat brain based on body/brain weight ratios, and a 2-to 3-year-old human brain corresponds to a post natal day-20 rat brain (11). Yet most NSC grafting studies have been performed over relatively short survival times of weeks to a few months in vivo (3,5,9,12).…”
Section: Introductionmentioning
confidence: 99%
“…ZIKV infection has been studied in WT neonatal mice (14,28,46,47). Neonatal mice may be useful models as key brain developmental processes in rodents occur postnatally, in contrast to the case for humans, where they occur during the third trimester of fetal development (48). Infection of 7-to 8-day-old WT C57BL/6 mice with ZIKV Dakar 41519 or ZIKV H/PF/2013 by subcutaneous or intraperitoneal injection resulted in central nervous system pathology and partial lethality (14,28).…”
mentioning
confidence: 99%